Cultura material y espacio doméstico: Mobiliario y menaje en el pueblo de Lambayeque durante los años 1750 – 1850. - Ruiz Cruzado, Saira (2019)
The present work had as purpose the knowledge of the subject furniture and kitchenware in the town of Lambayeque during the years 1750 to 1850, from the material culture having like objectives of investigation: to explain the urban transformation of Lambayeque of the Viceroyalty to the Republic, 1750 -1850; explain the development of the commercial exchange of furniture and household goods in the town of Lambayeque during the study period, explain the distribution of furniture and household items within the domestic space in the town of Lambayeque, taking into account the meaning and symbolic value 1750-1850 . _x000D_ This research explains the meaning and symbolic value that furniture and household furniture had within the domestic space, reflected in the changes and customs of people, and the acquisition of new appliances. As objects can not be isolated from the domestic environment, since this depends on their location within the home. Seven main spaces have been studied: main room, the platform, oratory, library, bedroom, kitchen and dining room. _x000D_ To achieve the work, bibliographic research techniques were used, using primary and secondary sources, with the purpose of analyzing and interpreting the data related to furniture and household items, the qualitative method to learn more about the distribution of the goods that people tested, economic, social level. And the comparative method between what establishes specialized historiography with the achievements of the research carried out. _x000D_ Finally, we conclude that the meaning and value of furniture and furnishings in Lambayeque during 1750 to 1850 varied according to social practices and periods of time. With the urban transformation of Lambayeque from the Viceroyalty to the Republic, more trade was generated that allowed the population to acquire new furniture and household items made with better materials and of higher quality; In addition, the development of local, regional and foreign trade helped the exchange of objects with more recent techniques and styles, which were destined to the houses that in turn was distributed according to the requirements and tastes of their owners to manifest their riches.